New‐onset atrial fibrillation incidence and associated outcomes in the medical intensive care unit. Issue 8 (6th July 2021) - Brunetti, Ryan; Zitelny, Edan; Newman, Noah; Bundy, Richa; Singleton, Matthew J.; Dowell, Jonathan; Dharod, Ajay; Bhave, Prashant D.
Abstract: Background: In patients with critical medical illness, data regarding new‐onset atrial fibrillation (NOAF) is relatively sparse. This study examines the incidence, associated risk factors, and associated outcomes of NOAF in patients in the medical intensive care unit (MICU). Methods: This single‐center retrospective observational cohort study included 2234 patients with MICU stays in 2018. An automated extraction process using ICD‐10 codes, validated by a 196‐patient manual chart review, was used for data collection. Demographics, medications, and risk factors were collected. Multiple risk scores were calculated for each patient, and AF recurrence was also manually extracted. Length of stay, mortality, and new stroke were primary recorded outcomes. Results: Two hundred and forty one patients of the 2234 patient cohort (11.4%) developed NOAF during their MICU stay. NOAF was associated with greater length of stay in the MICU (5.84 vs. 3.52 days, p < .001) and in the hospital (15.7 vs. 10.9 days, p < .001). Patients with NOAF had greater odds of hospital mortality (odds ratio (OR) = 1.92, 95% confidence interval (CI) 1.34–2.71, p < .001) and 1‐year mortality (OR = 1.37, 95% CI 1.02–1.82, p = .03). CHARGE‐AF scores performed best in predicting NOAF (area under the curve (AUC) 0.691, p < .001). Conclusions: The incidence of NOAF in this MICU cohort was 11.4%, and NOAF was associated with a significant increase in hospital LOS and mortality. Furthermore, the CHARGE‐AF score performed best in predicting NOAF.